Cognitive reserve and cognitive performance of patients with focal frontal lesions. (February 2017) - MacPherson, Sarah E.; Healy, Colm; Allerhand, Michael; Spanò, Barbara; Tudor-Sfetea, Carina; White, Mark; Smirni, Daniela; Shallice, Tim; Chan, Edgar; Bozzali, Marco; Cipolotti, Lisa
Abstract: The Cognitive reserve (CR) hypothesis was put forward to account for the variability in cognitive performance of patients with similar degrees of brain pathology. Compensatory neural activity within the frontal lobes has often been associated with CR. For the first time we investigated the independent effects of two CR proxies, education and NART IQ, on measures of executive function, fluid intelligence, speed of information processing, verbal short term memory (vSTM), naming, and perception in a sample of 86 patients with focal, unilateral frontal lesions and 142 healthy controls. We fitted multiple linear regression models for each of the cognitive measures and found that only NART IQ predicted executive and naming performance. Neither education nor NART IQ predicted performance on fluid intelligence, processing speed, vSTM or perceptual abilities. Education and NART IQ did not modify the effect of lesion severity on cognitive impairment. We also found that age significantly predicted performance on executive tests and the majority of our other cognitive measures, except vSTM and GNT. Age was the only predictor for fluid intelligence. This latter finding suggests that age plays a role in executive performance over and above the contribution of CR proxies in patients with focal frontal lesions. Overall, our results suggest that the CR proxies do not appear to modify the relationship between cognitive impairment and frontal lesions. Highlights: Effect of cognitive reserve (CR) proxies in focal unilateral lesions. NART IQ accounts for a larger proportion of variance in executive and naming skills. Age predicts performance on executive, fluid intelligence, speed and perception tests. Education and NART IQ did not modify the effect of lesion severity on cognitive impairment.